Migrasi dan Perlindungan Hak Asasi Imigran dalam Implementasi Prinsip Hukum Internasional Modern - Putri Amalia; Farhan Nugraha (Perkara : Jurnal Ilmu Hukum dan Politik, 2025)
The complexity of international migration governance continues to challenge the effectiveness of legal protection for immigrants in non-signatory states of the 1951 Refugee Convention, including Indonesia. Although Indonesia has shown administrative commitment through Presidential Regulation No. 125 of 2016, the legal framework remains limited and fragmented. This study aims to analyze the extent to which international legal principles are implemented within Indonesia’s domestic system and how institutional coordination affects immigrant protection. Using a normative-empirical legal method, the research examines 112 policy documents, court decisions, and field data covering the period from 2011 to 2023, supported by case comparisons with Malaysia and the Philippines. The findings reveal that 68 percent of immigrant cases in Indonesia rely on administrative mechanisms rather than formal legal protection, and regional implementation capacity varies significantly between provinces such as Aceh and Jakarta. The results also indicate that the lack of coordination among agencies contributes to a 42 percent delay in refugee registration and documentation processes. Comparative analysis shows that countries with direct legal ratification of the Convention provide more consistent protection and access to fundamental rights. The study contributes to the understanding of the relationship between moral commitment and legal enforcement in international law. The novelty of this research lies in its empirical demonstration of Indonesia’s partial adaptation of international refugee norms without formal ratification, offering a new framework for analyzing human rights protection in transitional legal systems.